Pengaruh Edukasi Gizi dan Permainan Ular TangGiz terhadap Pengetahuan Gizi Siswa/i SMA PGRI 2 Kota Jambi - Wulansari, Arnati; Putri, Darin Aini Avian; Ramlah, Siti; Hayati, Indah Puji; Sari, Indah Permata; Septyani, Dhea Putri; Munawaroh, Novia; Zafira, Audi Fitri (Universitas Baiturrahim, 2024)
Obesity is one of the most worrying health problems, especially for children and adolescents. Obesity in adolescents is caused by many factors, namely imbalanced diet, excess intake of macronutrients, frequent consumption of fast food, history of obesity in parents, and the habit of skipping breakfast. One of the causes of nutritional problems is due to lack of knowledge about nutrition which can then lead to mistakes in choosing food. Community service was carried out at SMA PGRI 2 Kota Jambi with 24 students as participants with an approach using an educational method with presentation (material presentation) and the game